Case Report: Hindlimb Ataxia Concurrent With Seizures by Presumed Osmotic Demyelination Syndrome in a Dog - Lee, Ga-Won; Kang, Min-Hee; Park, Hee-Myung (Frontiers in Veterinary Science, 2022)
A 6-year-old castrated male Chihuahua dog was presented with hindlimb paresis and ataxia. The dog had hyponatremia and was diagnosed as hypoadrenocorticism ten days before its visit, and the neurologic signs including generalized tonic seizures and hindlimb paresis occurred three days after correction of hyponatremia at a referral hospital. Based on history and clinical findings, osmotic demyelination syndrome (ODS) secondary to rapid correction of hyponatremia was highly suspected. After administration of anti-convulsant and supplements, seizures did not occur, and gait was normalized within two weeks. Phenobarbital was tapered and finally discontinued after three months, and seizure did not recur. The neurologic signs induced by ODS were completely resolved and the dog continued to be free of neurologic or additional clinical signs over the 19-month follow-up period. ODS should be included among the differential diagnoses in case of any acute neurological dysfunction that occurs with episodes of rapid correction of hyponatremia. To the author’s knowledge, this is the rare case report of a dog with hypoadrenocorticism and ODS after rapid correction of hyponatremia leading to neurologic signs including seizures and ataxia.